Gut microbiota changes and its potential relations with thyroid disorders - Vasconez, Paula A.; Rumipamba, Yesenia L.; Pineida, Maria Paula; Rodriguez, Paulina; Vargas, Yaritza Cardenas; Maggi, Esteban I.; Cifuentes, Paul Aguirre; Riofrio, Juan J. (International Journal of Research in Medical Sciences, 2025)
The human intestinal flora is composed of more than 1200 species of anaerobic and aerobic bacteria, along with bacteriophages, viruses and fungi, essential for several processes including digestive and non-digestive, being of vital importance for health, including digestive balance and immunological, hormonal and metabolic homeostasis. Micronutrients, generally trace elements (copper, iodine, iron, selenium, zinc) and vitamins (A, C, D and E), interact with the bacterial flora to generate an adequate immunological metabolism of the host. Multiple studies on the functioning of the gut microbiota (GM) have revealed an association between microbiota alterations and various pathological disorders, such as encephalitis due to antibodies against the N-methyl-D-aspartate receptor (NMDAR), anxiety, depression, early-onset cancer, type 1 diabetes, and type 2 diabetes. According to recent studies, the thyroid microbiota (TM) could play a fundamental role in the triggering of thyroid gland diseases, among which autoimmune diseases play an important role. Not only environmental triggers and predisposing genetic background cause autoaggressive damage, which affects the cellular and humoral networks of the immune system, but the GM interacts with distant organs through signals that may be part of the bacteria themselves or their metabolites. The objective of this review is to describe the current knowledge about the microbiota in the metabolism of thyroid hormones and the pathogenesis of thyroid diseases, as well as its participation in the appearance of benign nodules. and papillary cancer.